BIOLOGICAL RESPONSE MODIFIERS ACTIVITIES OF BUNI (ANTIDESMA BUNIUS)FRUITS FILTRATE TO ACTIVATED LYMPHOCYTES, MONONUCLEAR AND POLIMORPHONUCLEAR CELLS IN MALE MICE (RATTUS NORVEGICUS) WISTAR’S STRAIN INFECTED BY SALMONELLA TYPHIMURIUM - Gunarti, Gunarti; Jiwintarum, Yunan; Nurhidayati, Nurhidayati (Jurusan Analis Kesehatan, Poltekkes Kemenkes Mataram, 2014)
AbstractThis study aimed to know the natural activity of filtrate buni(Antidesma bunis)fruit as immunostimulant. Parameter of this activities was the number of activated lymphocytes, mononuclear and polimorphonuclear cells of mice wistar’s strain that infected by Salmonella typhimurium. The group of study consisted of 2 control groups, and 4 experiment group which given 25%, 50%, 75%, 100% dose of buni (Antidesma bunis)fruits filtrate for 7 days. The data resulted were statically calculated by Kruskal-Wallis test dan Mann-Whitney test. The result as number of activated lymphocytes in control group 1 and 2, and in treatment groups consecutivelly 1,5; 6,4; 8,4; 8,8 and 7,6. The analysis of hyphotesis by Kruskall_Wallis test resulted p= 0,000 (p<0,05), and the Mann-Whitney test showedthere was a significant differentiate among the control group and treatmen groups with p< 0,05.While, the number of PMN and MN cells, find no effect in basophils, but there is a significant effect of buni (Antidesma bunis)fruits filtrateto amount of netrofil, eosinofil, total polimorphonuclear cells; and lymphocyte, monocyte, and total mononuclear cells (p<0,05). Conclusion the filtrate of buni (Antidesma bunius) fruits was able to increase the number of activated lyphocytes; polymorphonuclear and mononuclearleukocytes in the male mice infected by Salmonella typhimurium significantly.Keywords: Biological Response Modifiers Activities, Buni (Antidesma Bunius)Fruits, Activated Lymphocytes, Mononuclear And Polimorphonuclear Cells, Salmonella Typhimurium.